The Impact of Maternal Employment on Infant Weight-, Length- and BMI-for-Age Based upon WHO Growth Chart Standards - A. Al-Zeidaneen, Safaa; S. Al-Bayyari, Nahla; A. Al-Zidaneen, Marwa (International Journal of Child Health and Nutrition, 2017)
Background: The infancy is a time of phenomenal growth and development. Infant of working mothers have a special concern as they have less time for their infant care. Objective: The present study aims to assess length, weight and BMI of Jordanian infants in nursery in reference to WHO growth chart standard for age Z-score and to study the impact of mothers’ work on their infant’s growth. Methods: A cross-sectional observational study was conducted on 92 infants aged between 3-12 months randomly and recruited from nurseries in Amman, Jordan. All selected infants their mothers are employed and working for at least 8 hour per day. The participants were divided according to gender (male; female) and age group as the following: 3-6 months; 7-9 months; and 10-12 months. Results: The prevalence of overweight or obesity was 15.2% in all studied infants. Overweight or obesity was more prevalent among female infants aged 3-6 months and among male infants aged 7-12 months. No infant (0.00%) regardless of gender or age group was underweight, stunting nor wasting per WHO standards of BMI for age z-score. Conclusion: Most infants of Jordanian working mothers seemingly have normal growth in weight and length and few of them were overweight or obese according to WHO standard of BMI for age z-score. These indicated that Jordan work polices support working mothers and their infants to have better health and development.